Acculturation identity and educational attainment - Lena Nekby; Magnus Rödin; Gülay Özcan (Institute for the Study of Labor (IZA), 2007)
This paper explores the identity formation of a cohort of students with immigrant backgrounds in Sweden and the consequences of identity for subsequent educational attainment. Unique for this study is that identity is defined according to a two-dimensional acculturation framework based on both strength of identity to the (ethnic) minority and to the (Swedish) majority culture. Results indicate that integrated men are associated with significantly higher levels of education than assimilated men. No differences in educational attainment are found between the assimilated and the integrated for women. These results put into question the premise of oppositional identities, i.e., a trade-off between ethnic identity and educational achievement, among immigrants in Sweden.
Keywords: J15; 330; Ethnic identity; acculturation; ethnic minorities; education; Ethnische Gruppe; Soziale Integration; Bildungsabschluss; Bildungsniveau; Schweden